The Effect of Liquidity, Leverage and Cash Flow on Financial Distress (Empirical Study on Food & Beverage Companies Listed in Indonesia Stock Exchange) - Jais, Elda Anggriani (Jurnal KIAFE, 2021)
This study aims to determine the effect of liquidity, leverage, and cash flow partially on financial distress in Food & Beverage Companies Listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The method used in the sample selection is purposive sampling, and obtained 15 samples from 30 companies that have met the sample criteria. The analytical method used in this study is logistic regression analysis with the help of IBM SPSS 25. The results of this study state that: (1) Liquidity has a negative effect on Financial Distress in Food & Beverage Companies listed on the Indonesia Stock Exchange in 2016-2020 (2) Leverage does not affect Financial Distress for Food & Beverage Companies listed on the Indonesia Stock Exchange in 2016-2020 (3) Cash Flow does not affect Financial Distress for Food & Beverage Companies listed on the Indonesia Stock Exchange in 2016-2020.Keywords: Liquidity, Leverage, cash flow, Financial Distress.